Effects of low light on photosynthetic properties, antioxidant enzyme activity, and anthocyanin accumulation in purple pak-choi (Brassica campestris ssp. Chinensis Makino). - Hongfang Zhu; Xiaofeng Li; Wen Zhai; Yang Liu; Qianqian Gao; Jinping Liu; Li Ren; Huoying Chen; Yuying Zhu (PLoS ONE)
Anthocyanins are secondary metabolites that contribute to red, blue, and purple colors in plants and are affected by light, but the effects of low light on the physiological responses of purple pak-choi plant leaves are still unclear. In this study, purple pak-choi seedlings were exposed to low light by shading with white gauze and black shading in a phytotron. The responses in terms of photosynthetic properties, carbohydrate metabolism, antioxidant enzyme activity, anthocyanin biosynthetic enzyme activity, and the relative chlorophyll and anthocyanin content of leaves were measured. The results showed that chlorophyll b, intracellular CO2 content, stomatal conductance and antioxidant activities of guaiacol peroxidase, catalase and superoxide dismutase transiently increased in the shade treatments at 5 d. The malondialdehyde content also increased under low light stress, which damages plant cells. With the extension of shading time (at 15 d), the relative chlorophyll a, anthocyanin and soluble protein contents, net photosynthetic rate, transpiration rate, stomata conductance, antioxidant enzyme activities, and activities of four anthocyanin biosynthetic enzymes decreased significantly. Thus, at the early stage of low light treatment, the chlorophyll b content increased to improve photosynthesis. When the low light treatment was extended, antioxidant enzyme activity and the activity of anthocyanin biosynthesis enzymes were inhibited, causing the purple pak-choi seedlings to fade from purple to green. This study provides valuable information for further deciphering genetic mechanisms and improving agronomic traits in purple pak-choi under optimal light requirements.